2001
DOI: 10.2134/agronj2001.1362
|View full text |Cite
|
Sign up to set email alerts
|

Upland Rice Response to Phosphorus Fertilization in Asia

Abstract: 1998). Traditional upland rice is adapted to soil acidity (Garrity et al., 1990; Wade et al., 1988); moreover, im-Upland rice (Oryza sativa L.) yields on infertile, acid soils in the provement in upland rice adaptation to soil acidity can Asian uplands average only 1 Mg ha Ϫ1 . Phosphorus deficiency is considered a major soil constraint to increased yield, but little quantitative be brought about by breeding (Zeigler et al., 1995; Kirk information is available. We analyzed P responses of traditional rice et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
3
22
2
Order By: Relevance
“…Similarly, Roder et al (1995a) also reported from one study that soil organic matter was associated with rice yield (r = 0.42), while in another study comparing high and low yielding areas in 55 fields, pH, total N, total C, extractable P and CEC were significantly higher in the high yielding areas. Unlike George et al (2001), extractable P measurements in this study were not correlated with rice yield, but there was a significant relationship with total P uptake.…”
Section: Soil Properties In Relation To Upland Rice Yieldscontrasting
confidence: 90%
See 1 more Smart Citation
“…Similarly, Roder et al (1995a) also reported from one study that soil organic matter was associated with rice yield (r = 0.42), while in another study comparing high and low yielding areas in 55 fields, pH, total N, total C, extractable P and CEC were significantly higher in the high yielding areas. Unlike George et al (2001), extractable P measurements in this study were not correlated with rice yield, but there was a significant relationship with total P uptake.…”
Section: Soil Properties In Relation To Upland Rice Yieldscontrasting
confidence: 90%
“…Shortened fallow periods have rendered these systems unsustainable as soil quality (due to nutrient depletion and erosion) is declining, weed pressure and labor inputs are increasing, and yields are declining with the end results being lower returns on productivity and increased poverty (Asian Development Bank, 2001;Linquist et al, 2005;Saito, 2005). The major soil fertility constraints in the Lao uplands are low N and P supply (George et al, 2001;Roder, 2001;Saito et al, 2006a,b).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with those reported by George et al (2001) who analyzed P responses of traditional rice varieties on farms in Laos, Thailand and the Philippines and improved varieties in researcher-managed experiments in the Philippines. Phosphorus fertilization significantly increased the yield, total biomass and P uptake in improved rice varieties, while the yield gain from on-farm P fertilization of traditional rice varieties was small.…”
Section: Phosphorus Response and Phosphorus Efficiency In Upland Ricesupporting
confidence: 92%
“…Drains of 0.4 m deep surrounded each field and plastic sheets were installed to 0.4 m depth in the bunds to separate the fields hydrologically. Flooded and aerobic fields were divided into one subplot receiving no fertilizer-N (0-N plot) and another subplot receiving 150 kg urea-N ha -1 (150-N plot) in three splits: 50 kg N ha )1 basal, 50 kg N ha (George et al, 2001). In the long-term experiment, several other cultivars were tested .…”
Section: Treatments and Designmentioning
confidence: 99%